PENYUSUNAN LAPORAN KEUANGAN UMKM BERBASIS SAK EMKM - Dabella Yunia; Galih Fajar Muttaqin; Windu Mulyasari; Kurniasih Dwi Astuti; Nana Nofianti; Tri Wahyudi; Muhammad Nawawi; Chandra Prasadhita (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Mataram, 2021)
The preparation of financial reports which has been seen as a difficult thing for Micro, Small and Medium Enterprises (MSMEs). The proposed community service program is a community service program that aims to provide easy solutions for Micro, Small, and Medium Enterprises in Banten Province in preparing financial reports. As a form of community service, community service was held with the theme